2015
DOI: 10.1371/journal.pgen.1005137
|View full text |Cite
|
Sign up to set email alerts
|

HOMER2, a Stereociliary Scaffolding Protein, Is Essential for Normal Hearing in Humans and Mice

Abstract: Hereditary hearing loss is a clinically and genetically heterogeneous disorder. More than 80 genes have been implicated to date, and with the advent of targeted genomic enrichment and massively parallel sequencing (TGE+MPS) the rate of novel deafness-gene identification has accelerated. Here we report a family segregating post-lingual progressive autosomal dominant non-syndromic hearing loss (ADNSHL). After first excluding plausible variants in known deafness-causing genes using TGE+MPS, we completed whole exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 40 publications
4
70
0
Order By: Relevance
“…Pure tone audiograms showed that six affected family‐202 members (aged 25‐65) possessed binaural mean thresholds >80 dB HL for stimuli of 1 to 8 kHz (Figure B). Corresponding to the thresholds of family‐202 members, in the European family, the youngest patient with hearing thresholds increased to 60 dB HL at 1, 2, 4 and 8 kHz was aged 28 to 29 . According to ARTA of the two families, the average ages with hearing thresholds ≥60 dB HL at mid and high frequencies were 10 years in family‐202 (Figure B), and over 40 years in the European family .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Pure tone audiograms showed that six affected family‐202 members (aged 25‐65) possessed binaural mean thresholds >80 dB HL for stimuli of 1 to 8 kHz (Figure B). Corresponding to the thresholds of family‐202 members, in the European family, the youngest patient with hearing thresholds increased to 60 dB HL at 1, 2, 4 and 8 kHz was aged 28 to 29 . According to ARTA of the two families, the average ages with hearing thresholds ≥60 dB HL at mid and high frequencies were 10 years in family‐202 (Figure B), and over 40 years in the European family .…”
Section: Resultsmentioning
confidence: 94%
“…The clinical manifestations of the two families were clearly different. In contrast to the European family, the earliest clinical evidence was obtained at an earlier age and hearing impairment was more severe in family‐202, namely, 7 years old with severe hearing loss (PTA = 63.75 dB HL) (Figure B) vs 8.6 years old with mild hearing loss (26 dB HL < PTA < 40 dB HL) in the European family . Pure tone audiograms showed that six affected family‐202 members (aged 25‐65) possessed binaural mean thresholds >80 dB HL for stimuli of 1 to 8 kHz (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations